2006
DOI: 10.1111/j.1399-0004.2006.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for MECP2 mutations in Spanish patients with an unexplained mental retardation

Abstract: Rett syndrome (RTT) is an X-linked progressive encephalopathy. Mutations in the MECP2 (methyl-CpG-binding protein) gene have been found to cause RTT. In the past few years, the role of MECP2 mutations in patients with mental disorders other than RTT has been studied, finding that mutations in MECP2 also contribute to non-syndromic entities. More recently, it has been demonstrated that RTT shares clinical features with those of Angelman syndrome, another neurodevelopmental disorder. These observations must be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Even when males with MECP2 have some of the distinctive features of RTT, such as loss of spoken language, loss of hand skills, or hand stereotypies, these features may be significantly subtler than those seen in females with RTT, further limiting specific clinical identification. This notion is borne out by MECP2 mutation studies of groups with neurodevelopmental delay that revealed mutations in 1.3–1.7% of males [Orrico, A. et al 2000, Couvert, P. et al 2001, Moncla, A.et al 2002, Yntema, H. G.et al 2002, Yntema, H. G.et al 2002, Bourdon, V.et al 2003, Kammoun, F.et al 2004, dos Santos, J. M.et al 2005, Ylisaukko-Oja, T.et al 2005, Donzel-Javouhey, A.et al 2006, Moog, U.et al 2006, Tejada, M. I.et al 2006], whereas few of these individuals were suspected as having MECP2 mutations. We expect that as whole exome or genome sequencing becomes commonly used to characterize males with neurodevelopmental disorders, it is likely that the identification of MECP2 mutations in these males will increase.…”
Section: Discussionmentioning
confidence: 99%
“…Even when males with MECP2 have some of the distinctive features of RTT, such as loss of spoken language, loss of hand skills, or hand stereotypies, these features may be significantly subtler than those seen in females with RTT, further limiting specific clinical identification. This notion is borne out by MECP2 mutation studies of groups with neurodevelopmental delay that revealed mutations in 1.3–1.7% of males [Orrico, A. et al 2000, Couvert, P. et al 2001, Moncla, A.et al 2002, Yntema, H. G.et al 2002, Yntema, H. G.et al 2002, Bourdon, V.et al 2003, Kammoun, F.et al 2004, dos Santos, J. M.et al 2005, Ylisaukko-Oja, T.et al 2005, Donzel-Javouhey, A.et al 2006, Moog, U.et al 2006, Tejada, M. I.et al 2006], whereas few of these individuals were suspected as having MECP2 mutations. We expect that as whole exome or genome sequencing becomes commonly used to characterize males with neurodevelopmental disorders, it is likely that the identification of MECP2 mutations in these males will increase.…”
Section: Discussionmentioning
confidence: 99%
“…Direct sequencing was used most often because MECP2 is a small gene (1.5 kb of coding sequence). Denaturing gradient gel electrophoresis, 12 denaturing highperformance liquid chromatography 47 or single-strand conformation polymorphism screening 52 were also used to screen large series of patients. These different techniques yield different mutation detection rates (between 0 and 3%).…”
Section: Screening Methodsmentioning
confidence: 99%
“…Similarly, known RTT-causing MECP2 mutations are found in patients who do not show classical RTT phenotypes (Suter et al 2013). Other than RTT, MECP2 mutations have been found in association with neurological/neuropsychiatric disorders such as, schizophrenia (Cohen et al 2002), FASD (Zoll et al 2004), PPM-X syndrome , autism , Prader-Willi syndrome (Tejada et al 2006) and Angelman syndrome (Watson et al 2001). These reports emphasize that the diagnosis of RTT as well as other MeCP2-related neurological disorders should not be limited to the detection of MECP2 mutations, but rather should be carried out in conjunction with clinical features.…”
Section: Mecp2 Mutations In Non-rett Syndrome Casesmentioning
confidence: 98%